Development of Multiple Representation Learning Videos on Hydrocarbon Nomenclature - Fatmala, Fatmala; Lestari*, Ira; Enawaty, Eny; Hairida, Hairida; Erlina, Erlina (Jurnal IPA & Pembelajaran IPA, 2024)
This research focuses on the development of learning media based on multiple representations in organic chemistry courses. Multiple representation-based learning media has the potential to improve students understanding of the concepts of chemical materials that are often considered difficult. However, the lack of learning media used by lecturers to discuss the three aspects of representation is a problem that needs to be addressed. This research aims to produce a nomenclature of hydrocarbon compounds learning video based on multiple representations and to find the eligibility and response for the developed learning video. The research methods are research and development using the 4d development model. The instruments used were the eligibility sheet and response questionnaire using a Likert scale. The eligibility for learning video is included as very feasible, with an average eligibility percentage of 95,03%. The eligibility of learning video was viewed in three aspects, namely, the lesson aspect (94.67%), the language aspect (95.56%), and the media aspect (94.87%). The responses given by students were included as a good category, as shown by the percentage of response results on the small-scale trial of 83,79% and large-scale trial of 83,31%. Based on the outcome of eligibility assessment and field trials, the nomenclature of hydrocarbon compounds learning video based on multiple representations is very feasible for learning media in the organic chemistry of monofunctional compounds course.